Workplace Loneliness: The Benefits and Detriments of Working From Home - Wax, Amy; Deutsch, Caleb; Lindner, Chloe; Lindner, Steven J.; Hopmeyer, Andrea (Frontiers in Public Health, 2022)
Self-determination theory posits that relatedness and autonomy are two drivers of work-relevant outcomes. Through the lens of this theory, the current study explored the potential interactive effects of relatedness and autonomy on affective, relational, and behavioral outcomes at work, operationalizing relatedness as workplace loneliness and autonomy as the ability to work from home. To test this relation, survey-based data from a sample of 391 working adults were collected and a path analysis was carried out. Results suggested that workplace loneliness negatively predicts affective organizational commitment, perceptions of coworker and supervisor support, organizational citizenship behaviors, and perceived performance. Furthermore, results suggested that workplace loneliness and working from home have an interactive effect on affective organizational commitment, perceptions of coworker support, and organizational citizenship behaviors. Specifically, working from home had a beneficial impact the relation between workplace loneliness and affective organizational commitment/perceptions of coworker support, but a detrimental impact on the relation between workplace loneliness and organizational citizenship behaviors. These results add to the extant body of scholarly work of self-determination theory by testing the theory in the post-pandemic context of working from home. In addition, these results have practical implications for managers, who should strive to create opportunities for employees who work from home to enact organizational citizenship behaviors.